PENGELOLAAN AIR TANAH BERBASIS KONSERVASI DI RECHARGE AREA BOYOLALI (Studi Kasus Recharge Area Cepogo, Boyolali, Jawa Tengah) - Riastika, Meyra (Jurnal Ilmu Lingkungan, 2011)
Groundwater potential in Boyolali District is very large, because it is situated on Karanganyar - Boyolali Groundwater Basin. This study was conducted in order to find an ideal form of conservation-based management to conserve ground water potential in Boyolali District by analyzing the condition of groundwater recharge area located in Cepogo and environmental problems in the area.This study used survey methods by measuring, interviewing, and observing the area, to obtain the facts occurring in the area. Result gained from the research are groundwater potential in Boyolali District is large enough with the total flow of the springs in Boyolali District to achieve 2.085 liter/sec, which is used for irrigation and clean water service taps. The potential of groundwater depends on its recharge area located in Cepogo. Sub district Cepogo which is located at elevation 700 - 1000 m above sea level, and the ground water level ranges between 10 – 50 m under the local ground. The environmental problems in groundwater recharge area Su district Cepogo are: land usage caused by the sand mining and the social culture farming.Groundwater conservation-based management based on PP No 43 Tahun 2008 proposed to be applied in recharge area Sub district Cepogo, Boyolali District, through: the protection and conservation of groundwater, preservation of groundwater, and quality management control of groundwater pollution. This is the Government responsibility in accordance with their authority and should be implemented by involving the communitySitus barbarslot terpercaya dengan berbagai pilihan permainan seru, peluang menang besar, dan fitur bonus menarik. Nikmati pengalaman bermain aman dan menyenangkan kapan saja!Barbarslot adalah salah satu situs resmi https://www.26barsandaband.com/videos/, 5rb dan depo 5k terbaru dengan beragam permainan terbaik tahun 2025.Nikmati pengalaman bermain https://www.carsoncityantiquemall.com/contact-3, grafis epik dan fitur bonus hadir untuk meningkatkan peluang kemenangan.Rasakan keseruan bermain di om88 dengan peluang menang yang lebih besar. Nikmati pengalaman bermain yang seru, aman, dan penuh tantangan. Segera coba dan raih kemenangan besarmu!Situs gacorqq adalah game yang sering memberikan kemenangan besar, meskipun hasilnya tetap acak, tak bisa diprediksi, dan bergantung pada keberuntungan pemain.Tempat terbaik hari ini untuk bermain game slot, dengan beragam permainan tersedia cukup dengan minimal deposit 5000 di situs gacorqq login, Anda dapat bermain sepuasnya dan kapan saja.Hadir untuk Anda slot deposit 5000, bersama situs gacor5000 raih kemenenangan mudah dan juga fasilitas game terlengkap beda dari lainnya.kumolojoyohttps://pn-batang.go.id/id/https://www.ppdkk.edu.my/https://cyclinic.com.tw/https://carriesbridalcollection.com/https://inspimate.co.ke/https://www.affluence-inf.com/https://socialmovementtechnologies.org/https://www.dac-hr.com/https://ican4ir.com/https://ucrnn.net/https://family-life.co/https://pelangideco.com/https://elsekgroup.com/https://icanleaduganda.com/https://lowveldfruits.co.za/https://dominionng.com/https://www.lwuc.org/https://acadasuite.com/https://noraktech.com/https://burocromatico.mx/https://norakle.com/https://downeyrootcanal.com/https://www.summit-smile.com/https://www.mycreativesmiles.com/https://appetito.uz/https://adsec.net/https://fahariloungemalindi.com/https://dahnanproperties.com/https://foresthydrology.gov.bc.ca/https://www.gebhardtforcolorado.com/https://gitlab.weather.noaa.gov/https://msoid.abom.org/https://www.rogeebeverlyhills.com/https://wasre-datamover.umaryland.edu/https://worthyfigures.com/https://www.helsingborgsakademin.helsingborg.se/https://saa.uinsgd.ac.id/https://designsbylillianj.com/https://www.tsv-einheit.de/https://starbuckspartnerhoursinfo.com/https://infosphereeducation.com/https://amandlaomnotho.com/https://puntacanard.do/https://alessandraquartaconte.com/https://sieudaga.com/https://horusservices.com.co/https://tiffanyqueen.store/https://accessstudentportal.com/https://www.fitlifefoundations.com/https://www.nukandy.com/https://filipinofoodcart.com/https://starbridgeguides.com/https://3beansart.com/https://www.iestpahtsihuas.edu.pe/https://worldoffoods.net/https://abejotaburnaby.cl/https://peoplesopioidsummit.com/https://voordeliggenieten.nl/https://bewealthyandjoyful.com/https://fabiananliker.com/https://ipracticegolf.com/https://lhbtiqontact.nl/https://maxdiscountcodes.com/https://stturtle.com/https://clickcatalystai.com/https://grubz.co.za/https://ir-terrasverwarming.nl/https://refael-group.co.il/https://www.thedriftlesssheep.com/https://yabolichina.com/https://www.gr4nt.com/https://moviestylepopcorn.com/https://pcavisen.dk/https://emersonart.com/https://surfessay.com/https://tuaton.com/https://chelsea-westside.com/https://jadejewlery.com/https://sencesecret.com/https://www.passticks.com/https://detucasa.online/https://davidrefael.co.il/https://refaelgroup.co.il/https://verygoodclean.com/https://www.knightvisor.com/https://klinkerhaus-am-wald.de/https://medicata.ee/https://refael-nadlan.co.il/https://www.bajioffer.com/https://buycyh.com/https://giuseppemagra.com/https://www.kutivzkouture.co.uk/https://lenyvankessel.nl/https://the-domains.com/https://thenativeborne.com/https://windowsandoors.co.uk/https://max-aperture.com/https://www.tacology101.com/https://paragontelco.com/https://dataleaked.com/https://brassringlineage.co/https://capelsoundhaven.com.au/https://goldcoastmecfs.com/https://sbtienda.com/https://shehealth.com/https://worldofteas.ca/https://mamieexcels.com/https://patriotluxpools.com/https://cascadesculinary.com/https://texasprideconcrete.com/https://recipetohappy.com/https://laalquiladora.com/https://thevpsacademy.com/https://ministry-websites.com/https://businesswebsiteservices.net/https://sqrealty.com.mx/https://emrooznama.com/https://hubbil.com/https://seoactions.com/https://testlang.com/https://thevinenetwork.com/https://yogaconmarcella.com/https://lakehouseufaula.com/https://elliotpro.com/https://nftgallerycenter.com/https://eastexhomecenter.com/https://culturallyresponsiveminds.com/https://leadgeeks.net/https://nextwavestrategies.ai/https://naju.us/https://roofingmasters.ca/https://smokemart.ca/https://www.maquette.ca/https://www.caraccidentattorneycolumbia.com/https://www.ergotijm.nl/https://www.earthyoga.store/https://acesdrains.com/https://agentedesegurosdesalud.com/https://asportdesigns.com/https://astatic-solutions.com/https://beattiepropertyservices.com/https://bigwestgiftsuite.com/https://bleroofing.com/https://bmugc.com/https://cardsandcrime.com/https://dharmasimple.com/https://ebolightmd.com/https://anovelidea.com.au/https://calvaryhill-lyman.org/https://eficon.cl/https://divinorigen.cl/https://einsparhelden.de/https://bulkbuydirect.store/https://www.caedenfetters.com/https://www.duncandigital.com/https://elixirclio.com/